2014
DOI: 10.1021/am502609c
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sn(S,Se) Secondary Phases in Cu2ZnSn(S,Se)4 Solar Cells: a Chemical Route for Their Selective Removal and Absorber Surface Passivation

Abstract: The control and removal of secondary phases is one of the major challenges for the development of Cu 2 ZnSn(S,Se) 4 (CZTSSe)-based solar cells. Although etching processes have been developed for Cu(S,Se), Zn(S,Se), and CuSn(S,Se) secondary phases, so far very little attention has been given to the role of Sn(S,Se). In this paper, we report a chemical route using a yellow (NH 4 ) 2 S solution to effectively remove Sn(S,Se). We found that Sn(S,Se) can form on the surface either because of stoichiometric deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
150
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 40 publications
13
150
2
2
Order By: Relevance
“…The degradation of FF at high Sn contents is associated with the appearance of Sn(S,Se) 2 secondary phase that segregates on top of the samples ( Figure S2, Supporting Information) and appears at Cu/Sn ratio < 1.65 in the absorber as measured by XRF. [18] At low Sn concentrations the devices show a degradation of V OC , J SC , and FF simultaneously, which is caused by shunting due to the formation of Cu x Se phases which occur at Cu/Sn ratios > 2.0 measured by XRF. [19] The bandgap trends of the kesterite layers are presented in Figure 3d as derived from the inflection point in the long wavelength region of the EQE.…”
Section: Resultsmentioning
confidence: 95%
“…The degradation of FF at high Sn contents is associated with the appearance of Sn(S,Se) 2 secondary phase that segregates on top of the samples ( Figure S2, Supporting Information) and appears at Cu/Sn ratio < 1.65 in the absorber as measured by XRF. [18] At low Sn concentrations the devices show a degradation of V OC , J SC , and FF simultaneously, which is caused by shunting due to the formation of Cu x Se phases which occur at Cu/Sn ratios > 2.0 measured by XRF. [19] The bandgap trends of the kesterite layers are presented in Figure 3d as derived from the inflection point in the long wavelength region of the EQE.…”
Section: Resultsmentioning
confidence: 95%
“…Despite these suitable optical properties and rising interest, there are difficulties in applying this material commercially as an absorber in solar cells. One of the major obstacles is the formation of secondary phases during the growth process, which can be detrimental to the solar cell performance [6,[10][11][12]. Therefore, it is important to investigate CZTSSe absorbers with a quick and non-destructive method to identify structural properties and the existence of secondary phases.…”
Section: Introductionmentioning
confidence: 99%
“…3 It has been shown that both etching with (NH 4 ) 2 S solution and using thermal evaporation during the annealing process are effective approaches for removing SnS on CZTS surface. 8 Regarding the CZTS rear, SnS could form due to the initial CZTS composition 23 as well as the back contact decomposition. 24 Therefore, to control the SnS formation on the CZTS rear, efforts to develop suitable CZTS composition and to passivate the back contact are required.…”
mentioning
confidence: 99%